Academic Senate Recording 2015-04-30 - Academic Senate:::::::::
This recording was digitized from cassette tapes. Chair Report. Agenda – Approved. Minutes of 4/16/15 – Approved. Consent item: Early Childhood Education Certificate – Approved. Questions for the President. Provost Report. Human Development Revision – First Reading completed. End of Year Report from the Professional Development Subcommittee. Direct Entry Masters of Nursing Discontinuance – First Reading. Vice President of Administration and Finance Report. Associated Students Report. Vice President of Student Affairs Report. Statewide Senators Report. Proposed change to the Senate formula for representation and duties of Senators – First Reading. CANDEL Discontinuance – Approved. EPC Report. FSAC Report. Good of the Order.